Psychosocial stress moderates the relationship between cerebrospinal fluid lactate dehydrogenase and the duration of untreated psychosis in first-episode psychosis - Giné-Servén, Eloi; Boix-Quintana, Ester; Daví-Loscos, Eva; Cepedello, Sandra; Moreno-Sancho, Lara; Niubó, Marta; Hernández-Antón, Rebeca; Cuesta, Manuel J.; Labad, Javier (Frontiers in Psychiatry, 2024)
Introduction:Previous research has shown that lower lactate dehydrogenase (LDH) concentrations in cerebrospinal fluid (CSF) are associated with longer prodromal symptoms in first-episode psychosis (FEP).We aimed to study whether there is a relationship between the duration of untreated psychosis (DUP) and LDH and other CSF biomarkers in FEP and whether stressful life events moderate this association.Methods:Ninety-five inpatients with FEP and with less than 6 weeks of antipsychotic treatment were included in the study.A lumbar puncture was performed at index admission to measure CSF parameters (glucose,total protein,LDH).The DUP was assessed with the Quick Psychosis Onset and Prodromal Symptoms Inventory.Stressful life events (SLEs) in the previous 6 months were assessed with the List of Threatening Experiences.We dichotomized the SLE variable into having experienced at least one SLE or no experience of SLEs.Statistical analyses were performed with SPSS v.25.0.Multiple linear regression analyses were conducted to explore the association between the DUP and CSF parameters (considered the dependent variable).Age,sex,DUP and SLEs were considered independent variables.We tested the DUP by SLE interaction.Significant interactions were included in the final model.The threshold for significance was set at p<0.05.Results:Fifty-four FEP patients (56.8%) reported an SLE in the previous 6 months.In the multiple linear regression analyses,we found a significant DUP by SLE interaction effect on CSF LDH concentrations (standardized beta= -0.320, t= -2.084, p= 0.040).In patients with SLEs,a shorter DUP was associated with higher CSF LDH concentrations and vice versa.Conclusions:Our study suggests that psychosocial stress moderates the relationship between the onset of psychosis and CSF biomarkers related to bioenergetic systems.